Analisa Faktor-Faktor yang Mempengaruhi Minat Generasi Z dalam Menggunakan Aplikasi Bank Digital di Indonesia - I Gede Wisnu Satria Chandra Putra; Jusia Amanda Ginting (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This research was conducted to become the basis for an effective service and application development strategy for digital banks to be able to attract Generation Z to use the services they offer. In this case, the author examines the influence of brand image factors, interface design and product features on the interest of Generation Z in using digital banking applications in Indonesia including blu, LINE Bank, Jago and SEA Bank. This research was conducted using statistical testing methods on data from questionnaires that were collected from 119 respondents. As a result, it was found that the three independent variables in this study had a significant positive effect simultaneously in influencing the interest of Generation Z in using digital banking applications. However, partially only the brand image and interface design factors have a significant positive effect, while the product feature variable does not have a significant positive effect on the interest of Generation Z to use digital bank applications due to the lack of unique features offered by digital bank applications when compared to conventional banks.